Correlation between Theory of Planned Behavior and Smoking Cessation: A Meta-Analysis - Mitha Amelia Rahmawati; Bhisma Murti; Hanung Prasetya (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: The increasing consumption of cigarettes that continues to occur among the community has an impact on the higher rates of morbidity and mortality. Active smokers who have a tendency to quit smoking can be identified by measuring their intentions. The theory of planned behavior is a concept that influences the study of an individual's behavior. This study aims to estimate the magnitude of attitudes towards behavior, subjective norms, and perceptions of behavioral control with behavior to stop smoking.Subjects and Method: This study is a systematic review and meta-analysis with the acronym PICO, namely population: smokers. Intervention: positive attitude toward behavior, supportive subjective norm, strong perception of behavioral control. Comparison: attitude towards negative behavior, subjective norms do not support, perception of behavior control is weak. Outcome: smoking cessation behavior. Data collection was obtained from 4 databases, namely: Google Scholar, PubMed, Science Direct and ProQuest with the keywords used